Variance of energy residual (VER): An efficient method for planetary gear fault detection under variable-speed conditions. (4th August 2019) - Park, Jungho; Kim, Yunhan; Na, Kyumin; Youn, Byeng D.
Abstract: Conventional methods used for fault detection of planetary gears are usually targeted for use with gears under constant speed conditions. Recently, some methods have been developed using an order-tracking method, or wavelet transform (WT), to detect planetary gear faults under variable-speed conditions. However, these previously studied techniques are computationally inefficient. Inefficiencies in these methods exist because 1) the order-tracking method of these techniques requires additional signal processing procedures, along with angle measuring devices, and/or 2) the WT process requires a lengthy computation time. Therefore, this study proposes a more efficient method, specifically a variance of energy residual (VER) method, for planetary gear fault detection under variable-speed conditions. The proposed VER method does not need angular information, and offers the potential to reduce computation time by using short-time Fourier transform (STFT) instead of WT. To demonstrate the performance of the proposed VER method, we calculated the fault sensitivity and computation time of the VER method using both simulation and experimental signals. From the results, it can be concluded that the VER method shows better fault sensitivity – with less computation time – than the previous method that uses WT. Graphical abstract: Image 103 Highlights: A new fault detection method is proposed for variable-speed planetary gears. The method could minimize the effect from variable-speed conditions. The method could reduce computation time from time-efficient time-frequency analysis. The method is validated using planetary gear data from the simulation and experiment. The method shows better performance than the previous methods.